Insulin-Reactive T Cells Convert Diabetogenic Insulin-Reactive VH125 B Cells Into Tolerogenic Cells by Reducing Germinal Center T:B Cell Interactions in NOD Mice - Pearson, James A.; Li, Yangyang; Majewska-Szczepanik, Monika; Guo, Junhua; Zhang, Li; Liu, Yu; Wong, F. Susan; Wen, Li (Frontiers in Immunology, 2020)
Insulin is a key autoantigen in Type 1 Diabetes (T1D), targeted by both T and B cells. Therefore, understanding insulin-specific T:B cell interactions is important. We have previously reported an insulin-reactive CD4+ T cell, (designated 2H6). Unlike other insulin-reactive T cells, 2H6 cells protect non-obese diabetic (NOD) mice from T1D development, mediated by TGFβ. To investigate insulin-specific T:B cell interactions, we bred 2H6αβ T cell receptor transgenic NOD mice (2H6) with the insulin-reactive B cell receptor transgenic NOD mice (VH125), generating 2H6VH125 NOD mice. Similar to 2H6 mice, 2H6VH125 mice are protected from T1D development. Interestingly, VH125 B cells did not alter the phenotype of 2H6 T cells; however, 2H6 T cells significantly altered the VH125 B cells by reducing the insulin-reactive non-germinal center (GC) and GC B cells, as well as MHC and costimulatory molecule expression on the B cells. Furthermore, the B cells in 2H6VH125 NOD mice exhibited increased non-insulin-specific and a class switched IgG isotype, which can be recapitulated in vivo in Rag-deficient NOD mice by adoptive transfer. In vitro, VH125 B cells from 2H6VH125 mice suppressed the proliferation of 2H6 T cells to insulin antigen but enhanced TGFβ secretion by 2H6 T cells from 2H6VH125 mice compared to 2H6 mice. In summary, our data showed that 2H6 CD4+ T cells alter the phenotype and function of insulin-reactive B cells from pathogenic to tolerogenic cells. In turn, VH125 B cells also modulate the function of the 2H6 T cells. Thus, promoting the interactions between antigen-specific regulatory T cells and B cells may lead to protection from T1D.